Valuing the Characteristics of Natural Gas Vehicles: An Implicit Markets Approach - Walls, Margaret A. (The Review of Economics and Statistics, 1996)
This paper estimates the costs of a government mandate to use natural gas vehicles, focusing on the less desirable attributes that these vehicles 9 possess. A model of producer and consumer behavior in a market for a differentiated product is constructed; a hedonic price function is estimated; and consumer surplus losses from the substitution of natural gas cars for gasoline cars are calculated. These losses are found to be significant: the average per car consumer surplus loss ranges from $1100 to $3200, with 20% to nearly 50% of the loss due to changes in vehicle characteristics. The costs of such a policy appear to be greater than the environmental benefits but may not be too far out of line with the costs of alternative approaches for reducing vehicular pollution. Copyright 1996 by MIT Press.